1997
DOI: 10.1021/bp970002w
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Shock Layer Theory to the Determination of the Mass Transfer Rate Coefficient and Its Concentration Dependence for Proteins on Anion Exchange Columns

Abstract: The extension of the shock layer theory to systems having a slow mass transfer kinetics and a concentration-dependent rate coefficient is discussed. Experiments were carried out with bovine serum albumin on two anion exchangers, TSK-GEL-DEAE-5PW and Resource-Q. The adsorption isotherm data, determined by single-step frontal analysis, could be fitted to simplified bi-Langmuir equations with very small residuals. A lumped kinetic model (solid film linear driving force model, with rate coefficient k f ) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 16 publications
5
34
0
Order By: Relevance
“…dependence of both km,L of BSA 17,18 and km of Tröger's base 19 reported previously [8][9][10][11] and derived new information concerning the mass transfer characteristics of the four transport processes described above. In the case of anion exchange separation of BSA, 17,18 it was shown that surface diffusion played a predominant contribution in the kinetic properties of mass transfer and that the linear concentration dependence of km,L probably resulted from that of the surface diffusion coefficient (Ds).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…dependence of both km,L of BSA 17,18 and km of Tröger's base 19 reported previously [8][9][10][11] and derived new information concerning the mass transfer characteristics of the four transport processes described above. In the case of anion exchange separation of BSA, 17,18 it was shown that surface diffusion played a predominant contribution in the kinetic properties of mass transfer and that the linear concentration dependence of km,L probably resulted from that of the surface diffusion coefficient (Ds).…”
supporting
confidence: 61%
“…The extent of the positive concentration dependence of km,L was larger for L-PA than for D-PA. It is expected that a more detailed analysis of the overall mass transfer rate parameter, km,L, could provide new, useful information and allow for a better understanding of the kinetic properties of imprinted stationary phases.A similar positive concentration dependence was also demonstrated for km,L in anion exchange chromatography of bovine serum albumin (BSA), 8,9 and for the mass transfer rate coefficient (km) in the enantiomeric separation of Tröger's base on microcrystalline cellulose triacetate. 10,11 In other previous publications, a concentration dependence was also confirmed for intraparticle diffusivity, 12 for tracer diffusivity, 13 for axial dispersion, 14 for effective diffusivity, 15 and for mutual diffusion coefficients.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In some cases, however, the use of these models can lead to some considerable model errors [5]. For example, Kaczmarski et al [6] re-evaluated, using the GR and the POR models instead of the transport model previously used [20,21], experimental data on the mass transfer kinetics of BSA in ion-exchange chromatography. They found that all these models could well account for experimental data, but the values of the mass transfer coefficients for the GR and the POR models did not depend on the concentration while those for the transport model did.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the MP model were calculated from experimental data by using Eqs. (19) and (20). The values of St9 for the POR model were obtained by using the fitting method and Eq.…”
mentioning
confidence: 99%